Hyperbaric Oxygen, Vasculogenic Stem Cells, and Wound Healing - Fosen, Katina M. (Mary Ann Liebert, Inc., 2014)
Significance: Oxidative stress is recognized as playing a role in stem cell mobilization from peripheral sites and also cell function. Recent Advances: This review focuses on the impact of hyperoxia on vasculogenic stem cells and elements of wound healing. Critical Issues: Components of the wound-healing process in which oxidative stress has a positive impact on the various cells involved in wound healing are highlighted. A slightly different view of wound-healing physiology is adopted by departing from the often used notion of sequential stages: hemostatic, inflammatory, proliferative, and remodeling and instead organizes the cascade of wound healing as overlapping events or waves pertaining to reactive oxygen species, lactate, and nitric oxide. This was done because hyperoxia has effects of a number of cell signaling events that converge to influence cell recruitment/chemotaxis and gene regulation/protein synthesis responses which mediate wound healing. Future Directions: Our alternative perspective of the stages of wound healing eases recognition of the multiple sites where oxidative stress has an impact on wound healing. This aids the focus on mechanistic events and the interplay among various cell types and biochemical processes. It also highlights the areas where additional research is needed. Antioxid. Redox Signal. 21, 1634–1647.